Caring Advanced Cancer Patients at Home During COVID-19 Outbreak: Burnout and Psychological Morbidity Among Palliative Care Professionals in Italy - Varani, Silvia; Ostan, Rita; Franchini, Luca; Ercolani, Giacomo; Pannuti, Raffaella; Biasco, Guido; Bruera, Eduardo (Journal of pain and symptom management, 2021)
Providing palliative care (PC) at home for patients with advanced cancer has become essential during the COVID-19 emergency. Nevertheless, the home PC professionals (PCPs) faced a challenging situation because of increased number of discharged patients, reduced availability of health-care facilities, and physical/relational barriers between them and patients. This study aimed to investigate the impact of COVID-19 pandemic on burnout and psychological morbidity among home PCPs in Italy. One hundred and ninety-eight PC physicians and nurses working in home assistance in Italy were invited to participate. The results obtained by the investigation conducted during the COVID-19 emergency (COVID2020) were compared with data collected in 2016 in the same setting (BURNOUT2016). The questionnaires (socio-demographics, Maslach Burnout Inventory and General Health Questionnaire-12) were the same for both the surveys. The PCPs participating in COVID2020 survey (n = 145) were mostly the same (70%) who participated in the BURNOUT2016 study (n = 179). One hundred and forty-five PCPs participated in the study (response rate 73.2%). During the COVID-19 emergency, home PCPs presented a lower burnout frequency (P < .001) and higher level of personal accomplishment than in 2016 (P = .047). Conversely, the risk for psychological morbidity was significantly higher during the pandemic (P < .001). In the age of COVID-19, the awareness of being at the forefront of containing the pandemic along with the sense of responsibility toward their high-risk patients may arouse PCPs' psychological distress, but, on the other hand, this condition may improve their sense of professional satisfaction and personal accomplishment.